2010
DOI: 10.1074/jbc.m110.163303
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Flow of Heliobacteria Is Related More to Clostridia than to the Green Sulfur Bacteria

Abstract: The recently discovered heliobacteria are the only Gram-positive photosynthetic bacteria that have been cultured. One of the unique features of heliobacteria is that they have properties of both the photosynthetic green sulfur bacteria (containing the type I reaction center) and Clostridia (forming heat-resistant endospores). Most of the previous studies of heliobacteria, which are strict anaerobes and have the simplest known photosynthetic apparatus, have focused on energy and electron transfer processes. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Here we report some unique and/or significant central carbon metabolic pathways and novel enzymes; details can be found in our recent published studies Feng et al, 2010b;Tang and Blankenship, 2010;Tang et al, 2009a;Tang et al, 2010a;Tang et al, 2010b;Wu et al, 2010).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Here we report some unique and/or significant central carbon metabolic pathways and novel enzymes; details can be found in our recent published studies Feng et al, 2010b;Tang and Blankenship, 2010;Tang et al, 2009a;Tang et al, 2010a;Tang et al, 2010b;Wu et al, 2010).…”
Section: Resultsmentioning
confidence: 91%
“…The methods for bacterial growth, physiological studies, gene expression profiles via quantitative realtime PCR (QRT-PCR) (Tang et al, 2009b) and enzyme assays of Roseobacter denitrificans (Tang et al, 2009a), Chlorobaculum tepidum (Tang and Blankenship, 2010;Tang et al, 2010a), Heliobacterium modesticaldum and Cyanothece sp. ATCC 51142 Wu et al, 2010) are described elsewhere.…”
Section: Physiological Studies and Integrative Genomicsmentioning
confidence: 99%
“…Furthermore, heliobacteria (a phylum of anaerobic anoxygenic phototrophic bacteria) were considered to have an incomplete reverse TCA cycle owing to their lack of a conventional CIT synthase. Recently, Tang et al [9] reported that the oxidative TCA route (OAA ! CIT !…”
Section: Central Metabolic Pathways For Carbonmentioning
confidence: 99%
“…The channelling can change isotopomer fingerprints because it may prevent the randomization of orientation for symmetric metabolites [83]. For example, the orientations of the TCA cycle metabolites (SUC and MAL) can be conserved in S. cerevisiae in the pathway from [4][5][6][7][8][9][10][11][12][13] C]a-ketoglutarate to OAA [84]. Because of the channelling of SUC/ fumarate formation enzymes (SucCoA synthetase, SUC dehydrogenase and fumarase), the 13 C fractions in the second and third carbon in OAA resulting from [4- C) have been used to investigate metabolite channelling and compartmentation in cytosolic and mitochondrial metabolite pools [82,85].…”
Section: Influential Factors In 13 C Metabolism Analysismentioning
confidence: 99%
See 1 more Smart Citation